Walk the Talk: The Effects of Apology and Reparation After Acts of Prejudice - Szanton, Elizabeth C.; Kodipady, Aditi; Onyeador, Ivuoma N.; Young, Liane (Journal of applied social psychology, 2025)
ABSTRACT In an era of abundant high‐profile apologies, many of which are perceived to be cheap and insincere, it is crucial to understand what constitutes a meaningful response from a high‐status perpetrator. Across three studies using a 2 (apology: present, absent) × 2 (reparation: present, absent) within‐subjects design, we presented participants (Ntotal = 300) with 16 vignettes describing prejudicial harm and assessed the unique effects of apology and reparation on perceptions of the perpetrators' subsequent responses. We additionally examined whether apology and reparation operate via a cognitive mechanism (reevaluation of the harm itself) or via a relational mechanism (identification with the perpetrator). As predicted, the presence of an apology and of reparation each independently predicted more positive perceptions of the perpetrator's response. Reparation exerted a stronger effect than apology on ratings of response quality (Study 1) and on ratings of the response's impact (Studies 2 and 3); in some cases, if reparation was present, apology did not add value. Our findings suggest that, while apology operates primarily via a relational mechanism, reparation operates via both cognitive and relational mechanisms. Additionally, responses were perceived more favorably overall in the context of close relationships (Study 3), which contributes to existing evidence that relational closeness buffers against negative attributions about the perpetrator and their motives. We suggest that while apology and reparation are each key to an effective response, reparation plays a particularly important role in predicting positive reception to a response to prejudicial harm.